2017
DOI: 10.3390/nu9040345
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intake of Grape Powder Prevents the Progression of Kidney Disease in Obese Type 2 Diabetic ZSF1 Rats

Abstract: Individuals living with metabolic syndrome (MetS) such as diabetes and obesity are at high risk for developing chronic kidney disease (CKD). This study investigated the beneficial effect of whole grape powder (WGP) diet on MetS-associated CKD. Obese diabetic ZSF1 rats, a kidney disease model with MetS, were fed WGP (5%, w/w) diet for six months. Kidney disease was determined using blood and urine chemical analyses, and histology. When compared to Vehicle controls, WGP intake did not change the rat bodyweight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The stained tissue sections were scanned with a Leica SCN400 Slide scanner (Leica Microsystems Inc., Concord, ON, Canada). Both the submesothelial thickness of the PM and glomerular injury of the kidney were quantitated using a Digital Image Hub – A slidepath Software Solution (Leica Microsystems, Inc.) in two separate tissue sections from each rat in a blinded fashion as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The stained tissue sections were scanned with a Leica SCN400 Slide scanner (Leica Microsystems Inc., Concord, ON, Canada). Both the submesothelial thickness of the PM and glomerular injury of the kidney were quantitated using a Digital Image Hub – A slidepath Software Solution (Leica Microsystems, Inc.) in two separate tissue sections from each rat in a blinded fashion as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…TXNIP is also overexpressed in the context of diabetes. Data from the literature identify TXNIP as a potential target in diabetes complications such as diabetic retinopathy, nephropathy, cardiomyopathy, and impaired post-ischemic revascularization [ 59 , 67 , 79 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ]. In a rat model of diabetic cardiomyopathy, TXNIP deletion in cardiomyocytes induces an improved inotropic response to β-adrenergic stimulation [ 144 ].…”
Section: Txnip Is a Multifunctional Proteinmentioning
confidence: 99%
“…Phytosterols have been demonstrated to exert antioxidant and anti-inflammatory effects, while polyunsaturated fatty acids were found to have anti-inflammatory activity [ 34 , 35 ]. In turn, Almomen et al [ 36 ] analyzed the beneficial effect of whole grape powder (WGP) in rats with CKD associated with a metabolic syndrome. Their study demonstrated lower proteinuria and urination as well as the reduction of common features present in early stages of diabetes-related CKD, such as mesangial expansion, glomerular atrophy tubular injury, and protein cast formation in the WGP-fed rats.…”
Section: Nutraceuticalsmentioning
confidence: 99%